Analisis Faktor-Faktor Penerimaan Layanan Streaming Musik di Indonesia - doddy ridwandono (Retii, 2019)
JOOX is an application that provides music streaming services. In Indonesia, Joox is ranked first on Google Play and Apple Store in the music and audio category. Based on these facts, it is important to reveal the factors that support the acceptance of Joox services. To to achieve the goal, Technology Acceptance Model (TAM) was used in this study. The Data was processed and analyzed using WarpPLS 6.0 software which were obtained from 400 Joox services users who filled out the online questionnaire. The results of the study revealed that: 1). Perceived of usefulness affects perceived satisfaction, 2). perceived ease of use affects perceived satisfaction, 3). perceived satisfaction affects perceived enjoyment, 4). perceived ease of use affects perceived of usefulness, 5). perceived ease of use affects perceived enjoyment, 6). perceived usefulness, perceived ease of, perceived enjoyment affect behavioral intention. Based on the results obtained, this study contributes to uncover the factors that influence technology acceptance, particularly in streaming music services. Discussions and suggestions for further research are discussed at the end of this paper.